Democracy and Anti-Corruption Strategy: The Role of Civil Society in Preventing and Combating Corruption in Indonesia* - Ratna Juwita, LL. M. (Association of Certified Fraud Examiners Indonesia Chapter, 2016)
ABSTRACTCorruption is an impediment to development and also amounts to a violation of human rights.1 The fight against corruption is a requirement in the good governance program.2 Civil society as the biggest stakeholder in a Statehas the prominent role in the fight againstcorruption.3 Indonesia placed at 107th rank in the Corruption Perception Index (CPI) and is one among states which are severely impededby corruption.4 Corruption in Indonesia is rampant and pervasive, several cases such as Cicak versus Buaya case and the appointmentof Budi Gunawan have attracted public attention massively.5 Indonesian civil society gunawan has actively engaged in the processes of these cases and their voice did make change, for example in the case of Cicak versus Buaya, the voice of civil society has led to the deponeering decision of Bibit and Chandera’s prosecution.6 This article aims to explain thelegal framework on the participation of civil society with regard to corruption prevention and to conceptualize the role of the civil societyin combating corruption by taking the evidence of emerging civil society and its relation to anti-corruption in Indonesia. This article alsoaims to explain the relationship between civil society, democracy and good governance as a strategic anti-corruption measures.